Damage assessment and blast vibrations controlling considering rock properties of underwater blasting. (September 2019) - Li, X.F.; Li, H.B.; Zhang, G.K.
Abstract: Underwater drilling blasting has significant vibrational attenuation effects compared to deep-hole blasting. The aim of this study is to propose a novel model for predicting peak particle velocity (PPV) considering the effects of the geological factor (i.e., weathering state), rock properties (i.e., rock quality designation) and engineering category (i.e., blasting on land or underwater) on the attenuation of the ground vibrations and frequency. A series of blasting experiments distributed over five sites were performed in the dredging engineering of the waterway at the Taishan Nuclear Power Plant. The geological investigation and the laboratory rock testing show that the weathering degree of the rock mass results in exponential increase in geological parameter α and linear increase in attenuation coefficient β . The impact of the high rock quality designation (RQD) puts limitations on the PPV attenuation, particularly for ground vibration induced by underwater blasting. The experimental results show that PPVs underestimated by the conventional equation (with a correlation coefficient of 64%) increase the risk of potential damage for protected objects. The novel predictor, formed by adding the depth ratio of the water to the scaled distance law suggested by Duvall and Fogelson, is verified by the agreement of the measurement data in this case with a correlation coefficient of 92%. Additionally, the frequency spectrum characteristics observed from blasting either on land or underwater are discussed. High-frequency components are found to be highly filtered due to the water sloshing underwater.